The Unstable Meaning of “Falling”: Woman Resistance On “Falling Star Challenge” Trend - Vita Amelia; Mita Rosaliza; Hesti Asriwandari (Human Sustainability Procedia, 2018)
The fall, which is always marked in its markers is to follow the gravity of the earth, which results in injuries or bruises, now experiencing meaningless instability, because social media framing is a sign of falling meaning that is no longer sick. Social media socializes unusual trends that are far from the real world. As with the "trend falling starch", which plagues social media. Instagram which is a media socializing the instability of the meaning of falling into a popular thing and does not feel pain when falling in the real world. This challenge stems from the crazy rich Russian act, the real reason is to show off what he has in the car and the things he carries scattered out of the car, arranged a bit messy, but the items are valuable and classy. This study analyzed the content descriptively with the subject of Instagram media studies with #fallingstarchallenge. It is found that 70% of women are resistant to this trend, this proves that women are very vulnerable to the various influences of trends they see and they watch on social media. This trend is a challenge for women to look more existent and keep up with the times. Even the markers and signs that Ferdinand de Saussure has about the concept of falling are able to be deconstructed into something that is no longer sick.